Nutrition and Dementia Ernährung und Demenz - Volkert, Dorothee (Aktuelle Ernährungsmedizin, 2019)
Nutrition and cognitive health mutually influence each other and are both important for the maintenance of independence and wellbeing up to old age. It is the aim of the present review to summarize the state of knowledge regarding the relation between nutrition and dementia and to highlight effective interventions to maintain adequate nutrition as long as possible. Various food components are known to be important for brain structure and functioning and related to cognitive performance. In epidemiological studies protective effects of adherence to a traditional Mediterranean diet on cognitive health are described. In the course of dementia sooner or later nutritional prolems appear which mostly lead to unbalanced and insufficient nutrition. Thus, nutritional interventions should be a fixed component of dementia treatment. They should be based on a routine screening for malnutrition, followed by assessment when appropriate, and periodic body weight control in order to recognize problems early. In all stages of dementia, an adequate oral nutrition can be supported by attractive, high-quality food according to individual preferences and needs served in a pleasant ambience, by adequate nursing support and treatment of underlying causes of malnutrition. If nutritional requirements are not met by usual food, oral nutritional supplements are recommended in order to improve nutritional status. Beneficial effects of energy and/or nutrient supplementation on cognitive abilities are however not proven. Artificial nutrition is only rarely indicated. In each case individual benefits and risks should be carfully weighed and the patients (presumed) will considered. In patients with advanced dementia and in the terminal phase of life artificial nutrition is not recommended.
CRIS-Team Scopus Importer:2019-05-17
Keywords: dementia; malnutrition; nutrition; nutritional intervention; tube feeding